CAUGHT IN THE ELECTION TRAP: VOTER FRAUDULENCE AND DYSFUNCTIONAL DEMOCRACY DURING THE 2021 ALBANIAN GENERAL ELECTIONS (Studia Politica. Romanian Political Science Review, 2025)
There is a growing consensus that data driven elections are a winner, irrespective of variables that may affect the elections. The question of how these data are obtained in the first place is highly disputed. This paper analyzes Albania and looks at one of its prime indicators like voter fraudulence that leads to distorted election results. Our findings show that the factors that have led to such an outcome are the patron-client relationship, shadow financing, and the use of public administration as an arm extension of the ruling party. There are many mechanisms used by ruling political parties in non-consolidated democracies to obtain an outright advantage in elections, ranging from political assassination or imprisonment of political opponents to staffing the ballot boxes. But as the Albanian case testifies, more refined measures are more legitimate both domestically and in seeking international legitimacy. This article advances the present debate on the impact of patronage schemes on electoral competition and results in semi-consolidated democracies.
Keywords: Dysfunctional democracy; voter fraudulence; distorted elections; Albania